A host–guest complexation based fluorescent probe for the detection of paraquat and diquat herbicides in aqueous solutions. Issue 121 (23rd November 2015) - Song, Gui-Xian; Tang, Qing; Huang, Ying; Wang, Ruibing; Xi, Yun-Yun; Ni, Xin-Long; Tao, Zhu; Xue, Sai-Feng; Zhang, Jian-Xin
Abstract : A new method based on fluorescence quenching of host–guest complexation was proposed for the determination of the two herbicides in river water and cabbages. The method is rapid, direct and simple. Abstract : The supramolecular interactions among thioflavin T (ThT), two herbicides paraquat (PQ) and diquat (DQ), and macrocyclic cucurbit[8]uril (Q[8]), were studied using spectrofluorimetry, ultraviolet-visible absorbance spectrometry, 1 H nuclear magnetic resonance spectroscopy, and isothermal titration calorimetry. A new method based on fluorescence quenching of the fluorescent host–guest complexes of Q[8]–ThT (the probe) upon cooperative binding with PQ or DQ to form a ternary complex, was proposed for the analytical determination of the two herbicides in aqueous solutions. Detection limits of 7.95 × 10 −9 mol L −1 and 8.07 × 10 −9 mol L −1 were obtained for PQ and DQ, respectively. Recoveries obtained by the proposed method in real-world examples such as river water and cabbage extracts were 104–108%. Interestingly, this method demonstrated high selectivity towards PQ and DQ in the presence of various metal ions and quaternary ammonium substances. Such a method provides a rapid, selective, sensitive and facile strategy for herbicides detection and quantification.